Competitiveness and comparative advantage in Hungarian agriculture - Imre Ferto; Lionel J. Hubbard (Hungarian Academy of Sciences, Institute of Economics, 2001)
We examine the competitiveness of Hungarian agriculture in relation to that of the EU, based on four indices of revealed comparative advantage, for the period 1992 to 1998. Consistency tests suggest that the indices are less satisfactory as cardinal and ordinal measures, but are useful in identifying whether or not Hungary has a comparative advantage in a particular product group. Despite significant changes in Hungarian agriculture during the 1990s, the results indicate that the pattern of comparative advantage has remained stable. Our findings suggest that Hungary has a comparative advantage for live animals and meat, but not for cereals, contradicting the findings of previous studies which have used different approaches to measuring competitiveness.
Keywords: 330